Association Between Body Mass Index and Mortality in Patients With Tuberculosis-HIV Co-Infection in Asia and Africa: A Systematic Review and Meta-Analysis Protocol - Irzal, Mufti As Siddiq M.; Wahyono, Tri Yunis Miko; Insani, Putri Novia Choiri; Loa, Welstin Wemi; Ngetwa, Leopardo Alvalius (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Globally, the prevalence of tuberculosis (TB) and human immunodeficiency virus (HIV) co-infection in 2019 was 8.2%. In 2020, TB-related deaths among individuals with HIV totaled 214,000, representing an increase from the previous year. Previous studies suggest that body mass index (BMI) is a significant predictor of mortality risk in individuals with TB and HIV co-infection, as malnutrition and low BMI are frequently linked to poorer clinical outcomes. This protocol has been developed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols (PRISMA-P) guidelines. A systematic review and meta-analysis will be conducted by searching three databases: MEDLINE/PubMed, Scopus, and ProQuest. This protocol aims to outline the stages and procedures of the forthcoming systematic review and meta-analysis, including the justification of the research question; the definition of Population, Exposure, Outcome, and Study design (PEOS); the inclusion and exclusion criteria; the search strategy; study screening and data extraction; and the planned data analysis. Identifying BMI as a prognostic factor through this study may inform nutrition-based interventions and treatment protocols aimed at reducing mortality among individuals co-infected with TB and HIV in Asia and Africa.